CLINICAL OUTCOMES OF SURGERY FOR ADVANCED STAGE RETINOPATHY OF PREMATURITY: A CASE REPORT - Yulia, Dian Estu; Jayawinata, Marissa; Hutapea, Mario Marbungaran (International Journal of Retina, 2023)
Introduction: Advanced stages of Retinopathy of Prematurity (ROP) could lead to childhood blindness and retinal surgery is needed as the main treatment. This case aims to report the clinical outcomes after surgery for advanced-stage ROP Case Report: A female infant was admitted to the pediatric ophthalmology clinic in Cipto Mangunkusumo National Central Hospital Jakarta with a lack of visual contact in both eyes at 53 weeks of Post Menstrual Age (PMA). The infant was delivered at 28 weeks of gestational age with a birth weight of 1100 g. The baby was treated in NICU for 24 days and received oxygen therapy in the previous hospital. Retinal examination revealed that the patient had stage 5 ROP in the right eye and stage 4B ROP in the left eye. Furthermore, blinking reflect was absent in both eyes. Vitrectomy and endolaser were performed for the baby’s left eye. Surgery was not conducted for the infant’s right eye due to poor prognosis. Six weeks after surgery, the infant underwent examination under anesthesia (EUA) which showed that the retina was reattached with no vitreous hemorrhage, and intraocular pressure measurement was 7 mmHg. The result of the visual acuity test by Cardiff Acuity Cards was 6/60 on both eyes. Followed up EUA reported that the refraction test result on the left eye was S-3.75 C-5.75 x 85o and an undetermined result on the right eye due to opacity in the visual axis. Discussion: Several surgeries have been described as the treatment of choice for advanced-stage ROP, including scleral buckling and vitrectomy with or without the addition of endolaser. Previous studies illustrated that stage 5 ROP has a low success rate on lens-sparing vitrectomy compared to stage 4A and 4B. The outcome success rate was the best in stage 4A ROP. Moreover, stage 4B ROP had a moderate success rate with sufficient visual outcomes. Conclusion: The functional outcome of vitrectomy surgery may not equate to anatomic success. Retinal reattachment and moderate visual outcome were achieved by performing vitrectomy and endolaser in this case. Followed-up periodically is necessary for advanced stage ROP postoperatively.